2016
DOI: 10.1002/2016jd025623
|View full text |Cite
|
Sign up to set email alerts
|

Implications of RCP emissions on future PM2.5 air quality and direct radiative forcing over China

Abstract: Severe PM2.5 air pollution in China and the First Grand National Standard (FGNS), implemented in 2016 (annual PM2.5 concentration target of less than 35 µg m−3), necessitate urgent reduction strategies. This study applied the nested‐grid version of the Goddard Earth Observing System (GEOS) chemical transport model (GEOS‐Chem) to quantify 2000–2050 changes in PM2.5 air quality and related direct radiative forcing (DRF) in China, based on future emission changes under the representative concentration pathway (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 113 publications
(157 reference statements)
6
34
2
Order By: Relevance
“…The aerosol DRF averaged over eastern China was −7.80 W/m 2 in 2012, which was slightly larger than the values (−4.8 to −6.08 W/m 2 ) estimated by previous studies J. W. Li et al, 2013;K. Li et al, 2016;Qian et al, Table S1.…”
Section: Radiative Forcing From Aerosols and Tropospheric O 3 In Chincontrasting
confidence: 56%
See 1 more Smart Citation
“…The aerosol DRF averaged over eastern China was −7.80 W/m 2 in 2012, which was slightly larger than the values (−4.8 to −6.08 W/m 2 ) estimated by previous studies J. W. Li et al, 2013;K. Li et al, 2016;Qian et al, Table S1.…”
Section: Radiative Forcing From Aerosols and Tropospheric O 3 In Chincontrasting
confidence: 56%
“…Li et al, ; K . Li et al, ; Qian et al, ) as listed in Table S1. These differences in estimated aerosol DRF can be caused by discrepancies in anthropogenic emissions, chemical mechanisms of the models as well as the treatment of aerosol optical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that MODIS retrievals tended to overestimate AOD in the NCP during polluted events compared with AERONET AOD [Gao et al, 2015;Li et al, 2016;Miao et al, 2016]. Therefore, we are mainly focused on the comparisons between simulated AOD values and AERONET observations in this work.…”
Section: Aerosol Optical Depthmentioning
confidence: 99%
“…In order to better understand the properties of atmospheric aerosols and their impacts, chemical transport models (CTMs) can be a critical tool, and they have been drawn up and applied to study various air pollution issues all over the world. For example, a fully coupled online Weather Research and Forecasting/Chemistry (WRF/Chem) model was developed by Grell et al (2005) and was used to study the aerosol-radiation-cloud feedbacks on meteorology and air quality (Gao et al, 2014;Zhang et al, 2015a;Qiu et al, 2017); a Models-3 Community Multi-scale Air Quality (CMAQ) modeling system was designed by the US Environmental Protection Agency (Byun and Ching, 1999) and was carried out to address acid deposition, visibility and haze pollution issues (Zhang et al, 2006;Han et al, 2014;Fan et al, 2015); a nested air quality prediction model system (NAQPMS) was developed by the Institute of Atmospheric Physics, Chinese Academy of Science (IAP/CAS) (Wang et al, 2001) for targeting at reproducing the transport and evolution of atmospheric pollutants in Asia (Li et al, 2012a;Wang et al, 2013c;Li et al, 2017a); a global three-dimensional chemical transport model (GEOS-CHEM) was first presented by Bey et al (2001) and was applied to study the source sector contribution, long-range transport and the prediction of future change in ozone and aerosol concentrations (Liao et al, 2006;Li et al, 2016b;.…”
Section: Introductionmentioning
confidence: 99%